Os escritos autobiográficos de Josef Mengele - Galle, Helmut (Estudos Avançados, 2011)
This article analizes autobiographical texts written by Josef Mengele during the years which he spent hidden in different places in the state of São Paulo. The material of about 500 pages in typoscript remains unpublished and deals with the first childhood years, the study of medicine in the Thirties, the imediate post-war period, when he worked under false name as a peasant in Bavaria and the beginning of his escape from Germany, but there is no reference to his brutal experiments with human beings in Auschwitz. Nevertheless, the slightly fictionalized texts provide some insight to this self-opionated person who kept the political positions without any sense of guilt and apparently even tried to convince his son - for whom the texts probably were written - by his ideologically saturated narrative. In certain passages, however, appears a kind of conscience of his inhuman acts, in disguised and perverse form, representing the very perpetrator in the roll of the victim.